2017
DOI: 10.4236/mri.2017.62002
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Cu/Zn-Superoxide Dismutase Levels in Hemodialysis Patients: A Mini Review

Abstract: Cu/Zn-superoxide dismutase (Cu/Zn-SOD) is an enzyme that is ubiquitously present in the cytoplasm and causes dismutation of superoxide radicals, therefore Cu/Zn-SOD is primarily used as an antioxidant marker. Levels of Cu/Zn-SOD are higher in the serum of hemodialysis patients than in serum of healthy volunteers. The increase of serum Cu/Zn-SOD levels is related to the decrease of kidney function with aging and arteriosclerosis in hemodialysis patients. Moreover, infection, vascular puncture, and hemostasis ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It should be noted that SOD-1 is primarily used as an antioxidant marker. However, the researchers found that because it is associated with many factors in HD patients, it could serve as a complex marker for atherosclerosis, vascular conditions, and inflammation [43]. It should be emphasized here that the research results regarding SOD are not conclusive.…”
Section: They Catalyze the Dismutation Of Omentioning
confidence: 86%
See 1 more Smart Citation
“…It should be noted that SOD-1 is primarily used as an antioxidant marker. However, the researchers found that because it is associated with many factors in HD patients, it could serve as a complex marker for atherosclerosis, vascular conditions, and inflammation [43]. It should be emphasized here that the research results regarding SOD are not conclusive.…”
Section: They Catalyze the Dismutation Of Omentioning
confidence: 86%
“…In opposition to SOD-1 (most of the results showed increased SOD-1 levels in HD), the lower SOD-2 content in mononuclear cells was associated with better survival in HD patients [43]. In uremic rats, Lim et al [45] discovered reduced SOD-2 in the liver, but Finsch et al found increased SOD-2 in the kidney [46].…”
Section: They Catalyze the Dismutation Of Omentioning
confidence: 99%
“…The results of the conducted study show that after a single session of the on-line hemodiafiltration with "high-flux" polysulfone membrane coated with vitamin E (Leocced 21H), the concentration of thiobarbituric acid reactive substances (TBARS) and the superoxide dismutase activity is significantly reduced. This can be explained by the effect of vitamin E, but also by the loss of microelement, the cofactor of the enzyme superoxide dismutase during the on-line hemodiafiltration session [25,26]. The results of the tests carried out so far show that a significant amount of microelements (selenium, zinc, copper) is lost during the on-line hemodiafiltration and hemodialysis with the "high-flux" polysulfone membrane, which results in a decrease in the activity of antioxidant enzymes, such as superoxide dismutase and glutathione peroxidase [27][28][29][30] while vitamin E is administered per os at a dose of 400-800 IU/day for 12-16 weeks for secondary prevention of cardiovascular events, and strong antioxidant effect is achieved at a dose of 1000 mg/day per os for 8 weeks (alpha tocopherol: 1.0 mg = 1.5 IU) [28][29][30].…”
Section: Discussionmentioning
confidence: 99%